2017
DOI: 10.1159/000480506
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Clinical Features and Outcomes of Acute Hepatitis E Viral Infections with Those of Acute Hepatitis A, B, and C Infections in Korea

Abstract: Objectives: This study investigated the etiology of acute viral hepatitis and compared the clinical features of hepatitis E virus (HEV) infections with those of other acute viral hepatitis infections in Korea. Methods: This study included 2,357 consecutive patients who were diagnosed with acute hepatitis, based on acute illness with jaundice or elevated alanine aminotransferase levels (>100 IU/L), between January 2007 and January 2016. Acute viral infections were observed in 23 (19.8%) patients with HEV, 49 (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…A study in Korea indicated that the median peak AST and ALT levels of patients with HEV infection were similar to those infected with HCV but lower than those infected with HAV and HBV. In contrast, the median peak total bilirubin levels in patients with HEV infections were similar to those infected with HAV and HBV but higher than those infected with HCV [ 36 ]. However, our study did not design to compare the liver function test among the four hepatitis viruses as the serum samples were recruited from patients initially suspected of HEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Korea indicated that the median peak AST and ALT levels of patients with HEV infection were similar to those infected with HCV but lower than those infected with HAV and HBV. In contrast, the median peak total bilirubin levels in patients with HEV infections were similar to those infected with HAV and HBV but higher than those infected with HCV [ 36 ]. However, our study did not design to compare the liver function test among the four hepatitis viruses as the serum samples were recruited from patients initially suspected of HEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…22 This is higher than the seroprevalence reported in studies from patients with liver disease in India (25.9%), Mongolia (29.2%), Sudan (30%) and Ethiopia (35.8%). 9,10,12,25 Studies amongst patients with chronic liver disease with smaller sample sizes have reported higher prevalence of 54.2% -61.4% from Ghana and India. 13,26,27 The presence of at least one serological marker of HBV infection in this study population (81.4%) agrees with reports from this region, where 70% -95% of adults have serological evidence of past exposure to this infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolytic anemia was reported in 23% of patients with acute E hepatitis as a complication of acute infection ( 134 ). During viral infection, patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency have lower level of glutathione, which leads to accumulation of oxidants and results in hemolysis during acute HEV infection ( 135 , 136 ). Only a few cases of autoimmune hemolytic anemia were described in patients with HEV, on the basis on clinical manifestation, hypersplenism, and positive direct antiglobulin test ( 137 , 138 ).…”
Section: Papers Selection Methodologymentioning
confidence: 99%